DISTRIBUSI RISIKO DAN MANFAAT PENGELOLAAN DAN PEMANFAATAN SUMBER DAYA ALAM DI DESA SATUI BARAT KABUPATEN TANAH BUMBU - Febrina Indrasari (LPPM Universitas Ekasakti Padang, 2023)
The guarantee of management and utilization of natural resources stated in the constitution should be the basis in managing the natural resources by taking into account the broad aspects of the interests of the community and the environment.This research aims to answer questions regarding the basis of the constitutional guarantee of management and utilization of natural resources in West Satui Village, Tanah Bumbu Regency towards environmental justice, and how the distribution of risks and benefits of management and utilization of natural resources in West Satui Village, Tanah Bumbu Regency. The research approach method used is doctrinal approach, with the target of norms, and linkages with facts found in the field. The result of this research is that unfair distribution of environmental risks will certainly lead to consequences in the form of environmental injustice. If the environment is damaged and unbalanced due to coal mining in Satui Barat Village, Tanah Bumbu Regency, it means that the risk is not felt by the government and mining business actors, but only a high risk for people's lives, as a result in terms of environmental risk distribution in coal mining in Satui Barat Village, Tanah Bumbu Regency can be said to be unfair.